Associação da má oclusão de Classe II Divisão 2 com anomalias do desenvolvimento dentário - Pereira, Pedro Mariano (2014)
NOTICE: this is the author’s version of a work that was accepted for publication in Revista Portuguesa de Estomatologia, Medicina Dentária e Cirurgia Maxilofacial. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Revista Portuguesa de Estomatologia, Medicina Dentária e Cirurgia Maxilofacial, [Vol. 53, Issue 4, (Out-Dec 2012)] DOI.10.1016/j.rpemd.2012.09.001